Intergenerational Trauma: A Scoping Review of Cross-Cultural Applications from 1999 to 2019 - Chou, Fred; Buchanan, Marla J. (Canadian Journal of Counselling and Psychotherapy, 2021)
It has been over 20 years since the publication of Danieli’s (1998) International Handbook of Multigenerational Legacies of Trauma, a seminal cross-cultural compilation examining the generational effects of mass trauma and intergenerational trauma (IGT). In the years since this book appeared, research on IGT has continued to be applied to many cultural groups, including those who have survived the Indian Residential Schools, the Khmer Rouge regime, or the Rwandan genocide. Previous reviews of IGT research have focused mainly on survivors of the Holocaust, which limits the cross-cultural application of this field of study. The purpose of this article is to provide a scoping review of scholarship published between 1999 and 2019 that aims to understand how IGT has been studied in cross-cultural applications. Overall, 29 articles were identified and reviewed. In light of the fact that cross-cultural perspectives on IGT are still emerging (Sirikantraporn & Green, 2016), the methodology and the cultural considerations described in this review can inform future cross-cultural IGT research.